2012
DOI: 10.5601/jelem.2010.15.4.771-788
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium as a nutritional tool of nitrogen efficient management - plant production and environment

Abstract: Nowadays, the main objectives of plant crop growers aim at two targets (i) increasing food production and (ii) simultaneously, reducing the environmental impact of increasing fertilizer nitrogen consumption. On a global scale, fertilizer nitrogen recovery ranges from 33 to 50%. The required efforts stimulating production but protecting the environment focus on increasing unit productivity of fertilizer N. Magnesium, owing to its biological functions in plants, should play a much more important role In modern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…In spite of this, the harvested YOI responded positively to magnesium fertilizers. This study confirms the hypothesis by Grzebisz et al (2010b) and Grzebisz (2013), concerning a supporting effect of applied magnesium on plant growth under conditions of a mild stress. This situation occurred just in 2008.…”
Section: Crude Oil Content and Yieldsupporting
confidence: 80%
“…In spite of this, the harvested YOI responded positively to magnesium fertilizers. This study confirms the hypothesis by Grzebisz et al (2010b) and Grzebisz (2013), concerning a supporting effect of applied magnesium on plant growth under conditions of a mild stress. This situation occurred just in 2008.…”
Section: Crude Oil Content and Yieldsupporting
confidence: 80%
“…However, nitrogen efficiency depends on other nutrients, which does not refer only to K, P, but also to S, Mg, and micronutrients. Therefore, the intensive production of this crop can be achieved provided a well-balanced supply of nutrients, including magnesium (Grzebisz et al 2010).…”
mentioning
confidence: 99%
“…TFP FN = 136 -7.07UPU for R 2 = 0.53 (15) The conducted divagation also showed that the classical index, i.e., agronomic efficiency, was only useful for describing the impact of nitrogen fertilizer on biomass productivity. The best model for this index can be developed to include magnesium and calcium as predictors: BE = 57.26 + 36.61TMgU -34.28TCaU…”
Section: Indices Of Nitrogen Use Efficiencymentioning
confidence: 99%
“…The rate of nitrogen uptake in this particular stage is driven by balanced uptake of other nutrients, such as potassium, phosphorus, and magnesium [15][16][17][18][19][20]. In modern staygreen varieties, the amount of nitrogen taken up by maize at the beginning of flowering constitutes around 50% of its final uptake [4,5,21].…”
Section: Introductionmentioning
confidence: 99%